Amphiphilic polymeric micelles as microreactors: improving the photocatalytic hydrogen production of the [FeFe]-hydrogenase mimic in water. Issue 3 (7th October 2015) - Wang, Feng; Wen, Min; Feng, Ke; Liang, Wen-Jing; Li, Xu-Bing; Chen, Bin; Tung, Chen-Ho; Wu, Li-Zhu
Abstract : An amphiphilic polymeric micelle is utilized as a microreactor to load a hydrophobic [FeFe]-hydrogenase mimic for photocatalytic hydrogen production in water. Abstract : An amphiphilic polymeric micelle is utilized as a microreactor to load a hydrophobic [FeFe]-hydrogenase mimic in water. The local concentration enhancement and strong interaction between the mimic and the photosensitizer as well as the water-mediated fast proton migration caused by the microreactor improve photocatalytic hydrogen production remarkably in water.